New International Development Banks and the Interests of Russia - V. L. Svedentsov (Мир новой экономики, 2018)
Development banks represent the conjunction of state structure and commercial bank. Nations are investors (shareholders) in them, as a rule, but funding to the borrowers is provided on the basis of payment and recurrency. Thus, the international development banks perform political and commercial functions in its activities. This article is devoted to analysis of the political and commercial features of the functioning of such new international and regional development banks like the Asian Infrastructure Investment Bank (AIIB) and the New Development Bank (NDB) and Russia’s interests in these financial institutions.